Determinants of Artificial Intelligence Effectiveness in Moroccan Public Institutions and Enterprises - Houda HANATY (International Journal of Scientific Research and Innovative Studies, 2025)
This study investigates the determinants of Artificial Intelligence (AI) effectiveness within Moroccan public institutions and enterprises. With the growing reliance on AI to improve operational efficiency, service quality, and decision-making, understanding the conditions that shape its successful adoption has become critical. Drawing on organizational, technical, technological, and regulatory perspectives, this research identifies the main factors that influence AI effectiveness, including leadership commitment, organizational culture, qualified human resources, infrastructure robustness, data quality, and regulatory frameworks. Methodologically, a mixed approach was employed, combining surveys and semi-structured interviews with public sector managers and employees. The findings reveal that leadership engagement and a culture of innovation are decisive drivers, while inadequate infrastructure, limited data accessibility, and regulatory uncertainties remain barriers. The study concludes by providing practical recommendations for strengthening AI integration through improved governance, enhanced training, and strategic partnerships. This paper contributes to the academic literature on AI in public administration while offering actionable insights for policymakers and practitioners in Morocco. Keywords Artificial Intelligence; Effectiveness; Moroccan Public Institutions; Organizational Factors; Technological Infrastructure; Data Quality; Governance; Public Sector Innovation. Received Date: February 25, 2025 Accepted Date: March 18, 2025 Published Date: April 01, 2025 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/449